Multi-stakeholder Dialogue Report on scaling CSA and climate services/data/innovations - Homann-Kee Tui, Sabine; Mutenje, Munyaradzi; Dube, Thabani; Makungwe, Mirriam; Ngwira, Amos (Accelerating Impacts of CGIAR Climate Research for Africa, 2023)
This Multi-Stakeholder Dialogue (MSD) was held on June 13, 2023, in Chipata, Eastern Zambia, as an opportunity for the Bundle 4 Accelerator Partnership, Diversified Integrated Mixed Chickens and Goats (Legume Systems), to reflect on progress and challenges and set new milestones for advancing agri-business, climate-smart agricultural practises, and information services. The MSD was hosted by the Chitetezo Cooperative Federation (CCF) and attended by CCF board members, coordinators, and farmers, as well as Community Markets for Conservation (COMACO) representatives; provincial government and advisory services; agriculture, forestry, seed systems, and fisheries provided technical knowledge and feedback to the discussions; provincial media covered the event. The CCF, in collaboration with COMACO, promotes inclusive agri-business development with strong participation of women in leadership and implementation. The CCF chair and several board members are women; more than 50% of women participate in activities, and several were present at the MSD. Promoting CCF means strengthening women in agribusiness and climate-smart agriculture. The MSD's aim was to strengthen the CCF's capacity to pursue its vision: To reduce poverty through nature-based solutions and agribusiness, driven by CCF as a self-organised sustainable cooperative movement in cooperation with COMACO. The dialogue centred around three core areas that require attention, investments, and networking to pursue this vision: (a) Agri-business capacity and leadership: strong leadership and governance systems and financial sustainability involving resource mobilisation are key for CCF to advance the cooperatives to profitable and self-sustaining entities. Identifying new and improving existing agri-businesses, building leadership, lobbying, and resource mobilisation capacity, and attracting new competences within the CCF are key areas that CCF members are committed to engaging in. (b) Seed systems and grain markets: improving the capacity of CCF farmers in seed multiplication as the main business and source of income for CCF while reaching out to cooperatives not yet involved in seed business. Branded seed packs are to be produced according to market requirements through agri-business incubation in cooperation with organisations such as the Seed Control and Certification Institute (SCCI), consultants, and ICRISAT. (c) Climate advisory services: It was highlighted that area-specific forecasts and advisories are missing, while the market is flooded by apps and tools that are not validated. In collaboration with the Zambia Meteorological Department (ZMD), rain gauges will be installed in all camps to validate the forecasts, and ZICTA will monitor and regulate the implementation of apps. Forecast seasons to extend to May to include post-harvest management decisions. In addition, presentations by ZMD and the Ministry of Livestock and Fisheries informed the CCF planning process. For CCF to drive the process that leads to their sustainability strategy, the working groups established detailed workplans and feedback mechanisms.